2015
DOI: 10.1016/j.ifacol.2015.10.270
|View full text |Cite
|
Sign up to set email alerts
|

Online Estimation of Ship's Mass and Center of Mass Using Inertial Measurements

Abstract: A ship's roll dynamics is sensitive to the mass and mass distribution. Changes in these physical properties might introduce unpredictable behavior of the ship and a worst-case scenario is that the ship will capsize. In this paper, a recently proposed approach for online estimation of mass and center of mass is validated using experimental data. The experiments were performed using a scale model of a ship in a wave basin. The data was collected in free run experiments where the rudder angle was recorded and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It was shown that the estimator is surprisingly robust in the desired parameters corresponding to mass and center of mass but that the other parameters had large variations. Although it has not been discussed in this paper, the proposed method has also been validated on data from scale model with good results, see Linder (2014) or Linder et al (2015).…”
Section: Sensitivity To Initial Conditionsmentioning
confidence: 96%
See 2 more Smart Citations
“…It was shown that the estimator is surprisingly robust in the desired parameters corresponding to mass and center of mass but that the other parameters had large variations. Although it has not been discussed in this paper, the proposed method has also been validated on data from scale model with good results, see Linder (2014) or Linder et al (2015).…”
Section: Sensitivity To Initial Conditionsmentioning
confidence: 96%
“…To simplify the analysis, all disturbances were set equal to zero. For a discussion on the estimator's disturbance rejection, see Linder et al (2014b), Linder et al (2014a) and Linder et al (2015). The system was assumed to be given by (11) and the parameters, given in Table2, were chosen to resemble the parameters of the scale model in Linder et al (2015).…”
Section: Sensitivity To Initial Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pendulum example has simple and intuitive dynamics that is a good approximation of the roll dynamics of many vehicles, such as cars, trucks or ships. In addition to the pendulum setup, the framework has been successfully applied to estimate a scale-model ship's dynamics which is considerably more complex, see Gustafsson (2015a) and(2015b).…”
Section: Experimental Verificationmentioning
confidence: 99%
“…The parameters of the mass and centroid can be measured by inertial measurement, multi-point weighing, a compound pendulum or a three-wire pendulum, and other experimental testing methods. Linder investigated a model of a ship’s roll dynamics along with measurements from an inertial measurement unit [ 8 ]. Bacaro developed a device for measuring the CG location of satellites by finite element modeling and analysis (FEA) and multi-body modeling and simulation (MBS) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%